HAK PEGAWAI NEGERI SIPIL YANG TERPIDANA KORUPSI (Studi Putusan PTUN Nomor 146/G/2019/PTUN-MDN) - Graceia Vidya Delphia; Andari Yurikosari (Reformasi Hukum Trisakti, 2021)
A Civil Servant, starting work as a Civil Servant Candidate in Central Tapanuli City, sued the Regent's Decree Number 2391/BKD/2018. After serving time in prison, the Plaintiff is still active again and receives a salary as a Civil Servant. normative juridical research, which is a descriptive analysis using secondary data which is analyzed qualitatively with a deductive method as a conclusion, based on the analysis carried out and it is concluded that 1) The basis uses article 87 paragraph 2 letter b of Law no. 5 of 2014 concerning ASN, the plaintiff must be dismissed as a Civil Servant 2) Based on Article 275 of Government Regulation Number 11 of 2017 concerning Management of State Civil Apparatuses for Civil Servants which has been proven convincing and valid through a Court Decision. Corruption Crimes need to be dishonorably discharged according to the President's procedures.